Gems and Jewelry Business in China: A Benchmark for Indian Businesses - Modi, Rishab (2008)
China has grown as a major producer of goods in the past couple of decades that has lead to a shift of production facilities from other countries to China. The Gems and Jewelry Industry has also witnessed such a trend, where major business from India shifted to China. Thus, the purpose of this research is to understand the reasons for the growth of China as a major producer and how it is a benchmark for Indian businesses.